Updates in the Management of Diabetic Macular Edema - Christopher Mathew; Anastasia Yunirakasiwi; Srinivasan Sanjay (Journal of Diabetes Research)
Diabetes mellitus is a chronic disease which has multiple effects on different end-organs, including the retina. In this paper, we discuss updates on diabetic macular edema (DME) and the management options. The underlying pathology of DME is the leakage of exudates from retinal microaneurysms, which trigger subsequent inflammatory reactions. Both clinical and imaging techniques are useful in diagnosing, classifying, and gauging the severity of DME. We performed a comprehensive literature search using the keywords “diabetes,” “macula edema,” “epidemiology,” “pathogenesis,” “optical coherence tomography,” “intravitreal injections,” “systemic treatment,” “hypertension,” “hyperlipidemia,” “anemia,” and “renal disease” and collated a total of 47 relevant articles published in English language. The main modalities of treatment currently in use comprise laser photocoagulation, intravitreal pharmacological and selected systemic pharmacological options. In addition, we mention some novel therapies that show promise in treating DME. We also review systemic factors associated with exacerbation or improvement in DME.